Evaluasi Efektivitas Peran dan Fungsi Audit Inernal (Studi Kasus pada Grup Perusahaan Farmasi Dipa Rajawali) - Sumantri Bratakusuma, SE., M.Ak. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2017)
This research aims to study the process of a paradigm shift or a view of the role and functions of internal audit, the cause of inefficiency function and role of internal audit in risk management, top management support and auditees of the findings of internal audit and process improvement and prevention is done in order to create corporate governance good. The object of research is a group company namely Dipa Eagles Pharmaceutical Group Company which is engaged in the fields of pharmaceuticals and medical devices. The study was conducted using a descriptive approach by comparing the analysis of the facts that occurred in the company's activities between theory and practice. From the results of field studies and literature, indicates that the Eagles Dipa Pharmaceutical Group has made the process of paradigm shift on the role and functions of internal audit of "watch dog" to "consultant" and partner for the company's management conducted by the Dept. Corporate Internal Audit. Although there has been a paradigm shift audits in Group Pharmaceutical Company Dipa Eagles, but yet there is conformity policy role and function of internal audit has been running in Group Pharmaceutical Company Dipa Rajawali so that the role and functions of internal audit can not be effective and have not been able to contribute to improvement internal control and risk management company. There has been no top management support and auditees of the findings obtained by the internal audit that good corporate governance in the Group of Pharmaceutical Companies Dipa Eagles has not been reached.